Analysis Of The Relationship Between Hand Washing Knowledge, Facilities And Infrastructure, Work Motivation, And Workload On Hand Hygiene Compliance Among Healthcare Workers At Mitra Medika Batanghari Hospital - Tampubolon, Efander; Rumengan, Grace; Nurhayati, Nurhayati; Agustin, Dinni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2024)
This study aims to analyze the relationship between handwashing knowledge, facilities and infrastructure, work motivation, and workload on the hand hygiene compliance of medical personnel at Mitra Medika Batanghari Hospital. This research employs a quantitative design with a cross-sectional survey method. The study sample consists of 98 medical personnel selected through purposive sampling. The instruments used in this study include: a hand hygiene knowledge questionnaire developed by Sego Soy (2019) and replicated by Bestari et al. (2024) and J et al. (2022); a motivation questionnaire based on Herzberg’s theory, compiled by Suseno Miftahun Ni’mah (2019); the modified NASA-TLX (National Aeronautics and Space Administration Task Load Index) by Ariyaya (2021) to measure workload; the Hand Hygiene Self-Assessment Framework 2010 from the World Health Organization (2010) to assess facilities and infrastructure; and a hand hygiene compliance questionnaire developed by Rofiani (2019). The analysis results show that all studied variables have a significant relationship with the hand hygiene compliance of medical personnel. This study concludes that increasing knowledge, providing adequate facilities and infrastructure, and enhancing motivation can improve medical personnel's compliance with hand hygiene. Keywords: Hand Hygiene Compliance, Handwashing Knowledge, Facilities and Infrastructure, Work Motivation, Workload, Medical Personnel